The Accuracy of Digital Impressions versus Conventional Impressions in Neonates with Cleft Lip and/or Palate: A Laboratory-Based Study - Jyotsna Unnikrishnan; Mahmoud Bakr; Robert Love; Ghassan Idris (MDPI AG, 2024)
Cleft lip and palate (CL/P) are a common congenital craniofacial anomaly requiring precise impressions for effective treatment. Conventional impressions (CIs) pose challenges in neonates with CL/P due to their delicate oral anatomy. While digital impressions (DIs) are increasingly recognised for their potential benefits over conventional methods in dentistry, their accuracy and application in neonates with cleft lip and palate (CL/P) remain underexplored. This study aimed to assess the accuracy of DIs compared to CIs in neonates with CL/P, using alginate and putty materials as references. A laboratory-based case-control study was conducted, utilising soft acrylic models resembling neonatal mouths with CL/P. Alginate and putty impressions were obtained conventionally, while digital impressions were captured using an intraoral scanner (IOS). A total of 42 models were analysed, divided evenly into three groups, with each group comprising 14 models. Superimposition and surface discrepancy analyses were performed to evaluate impression accuracy. The results revealed no statistically significant differences between the digital and conventional impressions in their intra-arch measurements and surface discrepancies. The mean measurement values did not significantly differ among groups, with p values indicating no significant variations (p > 0.05), confirmed by an analysis of variance. High intra-examiner reliability with Intra Class Coefficient (ICC) values close to 1 indicated consistent measurements over time. The current study demonstrates that DIs are equally accurate as conventional alginate and putty impressions in neonates with cleft lip and palate, offering a viable and less invasive alternative for clinical practise. This advancement holds promise for improving the treatment planning process and enhancing patient comfort, particularly in vulnerable neonatal populations. Further research is warranted to explore the clinical implications and factors affecting DI accuracy in this population.